Analisis Sosiolinguistik dalam Campur Kode Bahasa Arab: Studi Konten terhadap Penggunaan Campur Kode Bahasa Arab dalam Media Sosial (Grup WhatsApp): Sociolinguistic Analysis in Arabic Code Mixing: Content Study on the Use of Arabic Code Mixing in Social Media (WhatsApp Group) - Siti Maesaroh; Tatang, Tatang; Yunadi, Yunadi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study investigates the phenomenon of Arabic–Indonesian code-mixing within a Muslim community WhatsApp group through a sociolinguistic and critical discourse analysis (CDA) perspective. It aims to describe the forms of code-mixing, explore their social functions, and analyze the ideological meanings underlying the use of Arabic in online communication. Employing a qualitative approach with a case study design, the research focuses on one WhatsApp group consisting of 87 active participants. Data were collected through participant observation, documentation of group conversations, and semi-structured interviews to obtain in-depth and contextual information. Data analysis was conducted in two stages: typological analysis of code-mixing (Muysken, 2000) and critical discourse analysis based on Fairclough (2013). The findings show that insertion  is the dominant form of code-mixing, followed by alternation  and congruent lexicalization. The use of Arabic serves expressive, interactive, and symbolic functions, reinforcing religious identity, solidarity, and community cohesion. This phenomenon reflects the adaptation of classical diglossia into the digital context termed “digital diglossia” while simultaneously strengthening Islamic social, moral, and ideological values. The study contributes to the advancement of digital sociolinguistic research in Indonesia, deepens the understanding of Arabic as an index of identity, and provides practical implications for Arabic language learning based on social and digital cultural contexts.